E-commerce is a mechanism for promoting exports outside the field of Hydrocarbons in Algeria. - Chaabani, Nada; Laouameri, Oualid (Journal of Human Sciences, 2023)
E-commerce is considered one of the most important developments that the world has experienced, as it has become one of the main means that play an effective role in economic life. And as long as it was and is one of the most important urgent options to advance the national economy and free itself from dependence on oil as a volatile energy. From this point of view, in our study we will try to shed light on the legal system that has adopted this type of trade in Algeria and how this has contributed to the promotion of exports outside the hydrocarbon sector.